Changing Perceptions of Women's Honor: A Historical and Sociological Analysis - Afiq Husnun Azumah; Azizah Al Abiyyah; Azizah Khoirunnisa; Fathya Azzahra; Shofiyyah Shofiyyah; Febryan Hidayat (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
ufy